The Hybrid Fabrication Process of Metal/Silicon Composite Structure for MEMS S&A Device - Hu, Tengjiang (Micromachines (Basel), 2019)
The micro-electromechanical system (MEMS) safety-and-arming (S&A) device has the features of integration and miniaturization, which is one of the important directions of weapon development. Confined by the fabrication process, the silicon-based devices are too fragile, and the metal-based devices are low precision. In order to solve the contradiction between high precision and high structure strength, a metal/silicon composite structure is proposed in this paper, and a hybrid fabrication process is introduced. This new method mainly consists of metal sputtering, electroplating, and (inductively–coupled-plasma) ICP etching. As the resolution of the thick dry film is limited, the process of a femtosecond laser is applied to refine the structure, and the Ni plate (a block of 1 mm × 3 mm × 0.3 mm with a cavity of ϕ 0.85 mm × 0.3 mm in the center) is fabricated on the silicon-on-insulator (SOI) wafer successfully. After the double sides are etched by ICP, the SOI wafer is immersed in a buffered-oxide-etch (BOE) etchant to remove the buried layer. The cover plate acts as the encapsulation and is bonded with the SOI wafer by the epoxy glue. Then, the temporary support beam of the device is broken by the probe, and the suspended composite structure can be fully released. The hybrid process is the integration of the silicon-based process and the metal-based process, which can combine the advantages of both high precision and a high structure strength. The process proposed here is suitable for the application of weapon miniaturization.